HBV bypasses the innate immune response and does not protect HCV from antiviral activity of interferon - Mutz, Pascal; Metz, Philippe; Lempp, Florian A.; Bender, Silke; Qu, Bingqian; Schöneweis, Katrin; Seitz, Stefan; Tu, Thomas; Restuccia, Agnese; Koschny, Ronald; Polychronidis, Georgios; Schemmer, Peter; et al. (Gastroenterology, 2018)
Background & Aims - Hepatitis C virus (HCV) infection is sensitive to interferon (IFN)-based therapy, whereas hepatitis B virus (HBV) infection is not. It is unclear whether HBV escapes detection by the IFN-mediated immune response or actively suppresses it. Moreover, little is known on how HBV and HCV influence each other in coinfected cells. We investigated interactions between HBV and the IFN-mediated immune response using HepaRG cells and primary human hepatocytes (PHHs). We analyzed the effects of HBV on HCV replication, and vice versa, at the single-cell level. - Methods - PHHs were isolated from liver resection tissues from HBV-, HCV-, and human immunodeficiency virus-negative patients. Differentiated HepaRG cells overexpressing the HBV receptor sodium taurocholate cotransporting polypeptide (dHepaRGNTCP) and PHHs were infected with HBV. Huh7.5 cells were transfected with circular HBV DNA genomes resembling viral covalently closed circular DNA (cccDNA), and subsequently infected with HCV; this served as a model of HBV and HCV coinfection. Cells were incubated with IFN inducers, or IFNs, and antiviral response and viral replication were analyzed by immune fluorescence, reverse-transcription quantitative polymerase chain reaction, enzyme-linked immunosorbent assays, and flow cytometry. - Results - HBV infection of dHepaRGNTCP cells and PHHs neither activated nor inhibited signaling via pattern recognition receptors. Incubation of dHepaRGNTCP cells and PHHs with IFN had little effect on HBV replication or levels of cccDNA. HBV infection of these cells did not inhibit JAK-STAT signaling or up-regulation of IFN-stimulated genes. In coinfected cells, HBV did not prevent IFN-induced suppression of HCV replication. - Conclusions - In dHepaRGNTCP cells and PHHs, HBV evades the induction of IFN and IFN-induced antiviral effects. HBV infection does not rescue HCV from the IFN-mediated response.
Gesehen am 02.12.2019